Effect of Hydroethanolic Extract of Citrus Aurantium Leaves and Magnesium Sulfate in Mice Model of Vincristine-Induced Neuropathy: Citrus aurantium and Magnesium in Vincristine-Induced neuropathy - Bohlool Habibi; Tahereh Eteraf Oskouei; Haleh Vaez; Abbas delazar; Pouria Amani (Iranian Journal of Pharmaceutical Sciences, 2022)
Neuropathic pain due to vincristine administration is an important dose limiting adverse effect with no definite efficient treatment. Citrus aurantium possesses multiple therapeutic potentials and is commonly used in traditional medicine. This study investigate the possible effects of the hydroethanolic extract of C. aurantium (CA) leaves and magnesium sulfate (MgSO4) as a known analgesic in vincristine-induced peripheral neuropathy (VIN). Vincristine was administered intraperitoneally (IP) to establish peripheral neuropathy in mice. Effects of CA (50,100 and 150 mg/kg, IP) and MgSO4 (50, 75 and 100 mg mg/kg, IP) were assessed on pain threshold performed by hot plate test. Moreover, the serum levels of total antioxidant capacity (TAC) and malondialdehyde (MDA) were assayed. Administration of CA (100 and 150 mg/kg) showed significant (p<0.001) decrease in responses to pain. In addition, MgSO4 in high dose of 100 mg/kg could alleviate the neuropathic symptoms. The result of biochemical tests exerted high TAC level in all CA treated groups (p<0.01 in 50 mg/kg and p<0.001 for 100 and 150 mg/kg). MDA level was decreased significantly (p<0.001) by CA (100 and 150 mg/kg) and MgSO4 (100 mg/kg). However the combination of low dose of CA and MgSO4 exerted no efficient antinociceptive effect. According to the results, it can be concluded that MgSO4 and CA, in an effective dose range, can be effective in controlling the neuropathic pain followed by vincristine, possibly through the modulation of antioxidant balance directed by CA or the NMDA and calcium receptor blocking properties of MgSO4.